Non-destructive evaluation of the fibre content and anisometry in thin UHPFRC elements - Aurélio Sine (2020)
It is well known that the tensile response of UHPFRC is governed by the fibre content and orientation [1], [2]. This leads to an anisotropic tensile behaviour that needs to be characterized, especially in the case of thin elements or thin layers without conventional steel reinforcement. Here we present further developments on a non-destructive test (NDT) method [3] that allows determining suitable fibre content and anisometry indicators.